Parent-Teacher Communication from the Perspective of the Educator - Major, Enikő (Central European Journal of Educational Research, 2023)
Several, mostly quantitative, studies have already examined the relationship between teachers and parents, as well as the positive effects of parental involvement. The aim of this study is to explore how parental involvement is realized in communication between the two actors. In the framework of a qualitative study, semi-structured interviews were conducted with 31 teachers teaching in elementary schools, and the analysis was performed using the Atlas.ti software. Based on our findings, we concluded that regular communication, common language use, a positive attitude from both parties, and the appropriate use of information and communication technology tools are essential for effective communication. The practical significance of this is that teacher trainees should also emphasize practical education, with a special focus on their ability to establish appropriate communication with parents of different socioeconomic backgrounds.